Solid and macroporous Fe3C/N-C nanofibers with enhanced electromagnetic wave absorbability. Issue 1 (December 2018) - Liu, Huihui; Li, Yajing; Yuan, Mengwei; Sun, Genban; Liao, Qingliang; Zhang, Yue
Abstract A series of solid and macroporous N-doped carbon nanofibers composed of Fe3 C nanoparticles (named as solid Fe3 C/N-C NFs, solid Fe3 C/N-C NFs-1, solid Fe3 C/N-C NFs-2, macroporous Fe3 C/N-C NFs, macroporous Fe3 C/N-C NFs-1 and macroporous Fe3 C/N-C NFs-2, respectively) were prepared through carbonization of as-electrospun nanofiber precursors. The results show that the magnetic Fe3 C nanoparticles (NPs) dispersed homogeneously on the N-doped carbon fibers; as-prepared six materials exhibit excellent microwave absorption with a lower filler content in comparison with other magnetic carbon hybrid nanocomposites in related literatures. Particularly, the solid Fe3 C/N-C NFs have an optimal reflection loss value (RL ) of −33.4 dB at 7.6 GHz. For solid Fe3 C/N-C NFs-2, the effective absorption bandwidth (EAB) atRL value below −10 dB can be up to 6.2 GHz at 2 mm. The macroporous Fe3 C/N-C NFs have a broadband absorption area of 4.8 GHz at 3 mm. The EAB can be obtained in the 3.6–18.0 GHz frequency for the thickness of absorber layer between 2 and 6 mm. These Fe3 C–based nanocomposites can be promising as lightweight, effective and low-metal content microwave absorption materials in 1–18 GHz.